English

Prove that cot A1-cotA+tan A1-tanA = – 1 - Geometry Mathematics 2

Advertisements
Advertisements

Question

Prove that `"cot A"/(1 - cot"A") + "tan A"/(1 - tan "A")` = – 1

Sum

Solution

L.H.S = `"cot A"/(1 - cot"A") + "tan A"/(1 - tan "A")`

= `"cot A"/(1 - 1/(tan"A")) + "tan A"/(1 - tan "A")`

= `"cot A"/((tan "A" - 1)/(tan "A")) + "tan A"/(1 - tan "A")`

= `"cot A tan A"/(tan "A" - 1) + "tan A"/(1 - tan "A")`

= `1/(tan "A" - 1) + "tan A"/(1 - tan "A")`   ......[∵ cot A tan A = 1]

= `- 1/(1 - tan "A") + "tan A"/(1 - tan "A")`

= `- (1/(1 -tan "A") - "tan A"/(1- tan "A"))`

= `-((1 - tan "A")/(1 - tan "A"))`

= – 1

= R.H.S

∴ `"cot A"/(1 - cot"A") + "tan A"/(1 - tan "A")` = – 1

shaalaa.com
  Is there an error in this question or solution?
Chapter 6: Trigonometry - Q.3 (B)

RELATED QUESTIONS

9 sec2 A − 9 tan2 A = ______.


Prove the following trigonometric identities.

`tan theta - cot theta = (2 sin^2 theta - 1)/(sin theta cos theta)`


Prove the following trigonometric identities.

`(cos^2 theta)/sin theta - cosec theta +  sin theta  = 0`


Prove the following trigonometric identities.

`1 + cot^2 theta/(1 + cosec theta) = cosec theta`


Prove the following trigonometric identities.

tan2 A sec2 B − sec2 A tan2 B = tan2 A − tan2 B


Prove the following identities:

`(cotA - cosecA)^2 = (1 - cosA)/(1 + cosA)`


If `(cot theta ) = m and ( sec theta - cos theta) = n " prove that " (m^2 n)(2/3) - (mn^2)(2/3)=1`


If tan A =` 5/12` ,  find the value of (sin A+ cos A) sec A.


If `sec theta + tan theta = x,"  find the value of " sec theta`


\[\frac{\tan \theta}{\sec \theta - 1} + \frac{\tan \theta}{\sec \theta + 1}\] is equal to 


Prove that:

`(cot A - 1)/(2 - sec^2 A) = cot A/(1 + tan A)` 


Prove that `sqrt((1 + sin A)/(1 - sin A))` = sec A + tan A. 


There are two poles, one each on either bank of a river just opposite to each other. One pole is 60 m high. From the top of this pole, the angle of depression of the top and foot of the other pole are 30° and 60° respectively. Find the width of the river and height of the other pole.


Prove that: `(sec θ - tan θ)/(sec θ + tan θ ) = 1 - 2 sec θ.tan θ + 2 tan^2θ`


Prove that: sin6θ + cos6θ = 1 - 3sin2θ cos2θ. 


Prove the following identities.

sec6 θ = tan6 θ + 3 tan2 θ sec2 θ + 1


If sin θ + cos θ = `sqrt(3)`, then prove that tan θ + cot θ = 1


If sec θ + tan θ = `sqrt(3)`, complete the activity to find the value of sec θ – tan θ

Activity:

`square` = 1 + tan2θ    ......[Fundamental trigonometric identity]

`square` – tan2θ = 1

(sec θ + tan θ) . (sec θ – tan θ) = `square`

`sqrt(3)*(sectheta - tan theta)` = 1

(sec θ – tan θ) = `square`


Prove that `(cos^2theta)/(sintheta) + sintheta` = cosec θ


sec θ when expressed in term of cot θ, is equal to ______.


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×